Treatment of Extrahepatic Manifestations of Hepatitis C Virus - Degasperi, Elisabetta; Aghemo, Alessio; Colombo, Massimo (Clinics in liver disease, 2017)
Chronic infection with hepatitis C virus (HCV) is a multifaceted disease characterized by many extrahepatic manifestations (EHMs) that affect outcome and quality of life. HCV eradication by antiviral treatment has been proved beneficial in preventing the development of EHMs and is also able to improve many HCV-related severe disorders and neurocognitive outcomes and quality of life. Until recently, antiviral therapy of EHMs was limited to the presence of interferon-based treatment, and was contraindicated in many patients because of hematologic toxicity or risk of exacerbating immune-mediated disorders. The availability of interferon-free regimens solves this issue allowing for enhanced safety and efficacy to provide universal treatment of HCV-related EHMs.